Clinical study of post-operative complications of various stomas (ileostomy versus colostomy) for obstructing distal colorectal malignancies in an emergency setting: a prospective hospital-based study - Wani, Safoora; Gilkar, Ishfaq Ahmed; Wani, Yaser Hussain; Nowreen, Farzanah; Thakur, Shiwani; Bashir, Younis (International Surgery Journal, 2020)
Background: This study aims to provide an overview of all complications that may occur after construction of an ileostomy or colostomy (loop or end) for obstructing distal colorectal malignancy in emergency setting. Methods: It was a prospective observational study. Forty-eight patients were included in this study. Patients were divided into two groups, group (A) included patients with ileostomies (number of patients=24) and group (B) included patients with colostomies (number of patients=24). Results: Most common age group in both groups was >60 years, Peristomal skin irritation occurred in 33% of patients who have undergone ileostomy and 13% of patients who had undergone colostomy. 4% of patients who had undergone ileostomy developed retraction of the stoma. None of the patients who underwent colostomy developed retraction of stoma, 17% of patients who had undergone colostomy developed stomal prolapse; Stoma prolapse was seen in only 5% of patients who had undergone ileostomy. Conclusions: Stoma formation is a frequently performed surgical procedure. Ileostomy and colostomy are the most commonly made stomas in surgical practice. Ileostomies have slightly higher complication rate than colostomies. Peristomal skin irritation is the most common complication among all the complications. The second most common complication is stomal prolapse.